Electrochemical Behavior of Linico Oxide Cathodes as Catalyst for Lithium-Air Batteries - Gautier-Zamora, J; Gautier-Zamora, J; Herrera-Diaz, F; Herrera-Diaz, F (Springer Science and Business Media Deutschland GmbH, 2025)
Three LiNixCo2-xOδ (x = 0, 0.5, 0.75)-mixed oxides were synthesized via thermal decomposition of nitrate salts in aqueous solution and characterized by X-ray diffraction (XRD), confirming a spinel structure with space group Fd3m. Previously investigated as lithium insertion cathodes, these oxides were evaluated for potential application as catalysts in lithium-air batteries. This study analyzes the electrochemical behavior of these materials in a 1 M LiOH electrolyte solution, using electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). EIS results indicated higher energy storage capacities for compositions with increased nickel content, with capacitances of 0.91 mF for x = 0.5 and 1.21 mF for x = 0.75, and corresponding charge transfer resistances (Rct) of 110 and 93 ohms. CV analysis showed significant redox activity, particularly in oxygen reduction and evolution reactions. The x = 0 composition displayed reduction peaks at − 0.96 V, − 1.614 V, and − 2.118 V vs SHE, and oxidation peaks at − 1.188 V, 0.924 V, and 1.416 V vs SHE. Additional peaks were observed for the x = 0.5 and x = 0.75 compositions, indicating more complex redox behavior due to nickel presence. These findings demonstrate a clear correlation between the ionic composition of Li-Ni-Co spinel oxides and their electrochemical performance, especially in terms of energy storage and redox processes. This research highlights the potential of these materials as cathodes in lithium-air batteries, contributing to the development of energy storage systems with enhanced efficiency and performance. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.